The Shakespeare Brand in Contemporary “Fair Verona” - Oggiano, Eleonora (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
The idea that Shakespeare belongs to the world is certainly not new. From the beginning of his afterlife as a dramatist two issues have been consistently put forward by his contemporaries: 1) his art’s universality—for Ben Jonson, Shakespeare was the one “To whom all scenes of Europe homage owe”—and 2) his ability in appropriating foreign exotic environments which have notoriously characterised most of his plays. The value of such claims, which seem to be so present to us, helped to identify Shakespeare as an ‘universal’ icon whose work transcends time and space, gradually fostering, in and outside Britain, the so-called ‘Bardification of culture’, a phenomenon which persists, even more powerfully, nowadays. This study examines the different ways through which Verona has contributed in popularizing and elaborating the myth of Romeo and Juliet into a variety of formats suitable for the tourism market. By taking into account the so-called ‘Shakespace’ phenomenon, it focuses on what I have labelled as the ‘R&J-influenced spaces’ which account for a number of civic, cultural, and narrative spaces generated by and constructed upon the myth of the Veronese lovers.